Cartographic Image of Changes in Population Distribution as an Indicator of Peripherality - Paweł Cebrykow; Małgorzata Flaga; Mirosław Krukowski (Barometr Regionalny, 2015)
The article discuss a thesis stating that the most credible “markers” of peripherality constitute indicators referring to demographic changes, particularly depopulation related to migration, the resulting decrease in the size of population, and consequently changes in the population density. Such an assumption is based on the commonly acknowledged fact that the most intensive depopulation occurs in areas distinguished by low quality and level of life resulting from restricted accessibility and a low level of socio-economic development. The presented hypothesis is verified by analysis of maps presenting demographic changes in Poland after World War II.